Survey of diagnostic and treatment practices for multiple sclerosis in Europe. (31st January 2017) - Fernández, O.; Delvecchio, M.; Edan, G.; Fredrikson, S.; Gionvannoni, G.; Hartung, H.‐P.; Havrdova, E.; Kappos, L.; Pozzilli, C.; Soerensen, P. S.; Tackenberg, B.; Vermersch, P.; et al.
Abstract : Background and purpose: Up‐to‐date information is needed on the extent to which neurologists treating multiple sclerosis (MS) in Europe are integrating rapidly evolving diagnostic criteria, disease‐modifying therapies and recommendations for monitoring disease activity into their clinical practice. Methods: A steering committee of MS neurologists used a modified Delphi process to develop case‐ and practice‐based questions for two sequential surveys distributed to MS neurologists throughout Europe. Case‐based questions were developed for radiologically isolated syndrome (RIS), clinically isolated syndrome (CIS), relapsing−remitting MS (RRMS) and RRMS with breakthrough disease. Results: Multiple sclerosis neurologists from 11 European countries responded to survey 1 ( n = 233) and survey 2 ( n = 171). Respondents agreed that they would not treat the patients in the RIS or CIS cases but would treat a patient with a relatively mild form of RRMS. Choice of treatment was evenly distributed among first‐line injectables and oral treatments for mild RRMS, and moved to second‐line treatment as the RRMS case increased in severity. Additional results on RRMS with breakthrough disease are presented. Conclusions: Although there was general agreement on some aspects of treatment, responses to other management and clinical practice questions varied considerably. These results, which reflect current clinical practice patterns, highlight the need for additional MS treatment education and awareness and may help inform the development of MS practice guidelines in Europe.